Targeting prostate cancer cell lines with polo‐like kinase 1 inhibitors as a single agent and in combination with histone deacetylase inhibitors. Issue 10 (24th July 2013) - Wissing, Michel D.; Mendonca, Janet; Kortenhorst, Madeleine S. Q.; Kaelber, Nadine S.; Gonzalez, Matthew; Kim, Eunice; Hammers, Hans; van Diest, Paul J.; Carducci, Michael A.; Kachhap, Sushant K.
Abstract : Combinations of anticancer therapies with high efficacy and low toxicities are highly sought after. Therefore, we studied the effect of polo‐like kinase 1 (Plk1) inhibitors on prostate cancer cells as a single agent and in combination with histone deacetylase (HDAC) inhibitors valproic acid and vorinostat. IC50 s of Plk1 inhibitors BI 2536 and BI 6727 were determined in prostate cancer cells by MTS assays. Morphological and molecular changes were assessed by immunoblotting, immunofluorescence, flow cytometry, real‐time RT‐PCR, and pulldown assays. Efficacy of combination therapy was assessed by MTS and clonogenic assays. IC50 values in DU145, LNCaP, and PC3 cells were 50, 75, and 175 nM, respectively, for BI 2536 and 2.5, 5, and 600 nM, respectively, for BI 6727. Human prostate fibroblasts and normal prostate epithelial cells were unaffected at these concentrations. While DU145 and LNCaP cells were solely arrested in mitosis on treatment, PC3 cells accumulated in G2 phase and mitosis, suggesting a weak spindle assembly checkpoint. Combining Plk1 inhibitors with HDAC inhibitors had synergistic antitumor effects in vitro . DMSO‐treated prostate cancer cells were used as controls to study the effect of Plk1 and HDAC inhibition. Plk1 inhibitors decreased proliferation and clonogenic potential of prostate cancer cells. Hence, Plk1 may serve as an important molecular target for inhibiting prostate cancer. Combining HDAC inhibitors with BI 2536 or BI 6727 may be an effective treatment strategy against prostate cancer.—Wissing, M. D., Mendonca, J., Kortenhorst, M. S. Q., Kaelber, N. S., Gonzalez, M., Kim E., Hammers, H., van Diest, P. J., Carducci, M. A., Kachhap, S. K., Targeting prostate cancer cell lines with polo‐like kinase 1 inhibitors as a single agent and in combination with histone deacetylase inhibitors. FASEB J. 27, 4279–4293 (2013). www.fasebj.org